2009
DOI: 10.1590/s0100-204x2009000500009
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de formononetina na colonização e esporulação de fungos micorrízicos em braquiária

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de aplicações de Mycoform na colonização micorrízica e esporulação de 13 isolados de fungos micorrízicos arbusculares em Brachiaria decumbens. O experimento foi conduzido em casa de vegetação, em solo esterilizado, com delineamento experimental inteiramente casualizado, em arranjo fatorial 3x13, com cinco repetições. O produto foi aplicado no plantio e foi ou não aplicado uma segunda vez 60 dias depois, na quantidade de 2 mg kg -1 de solo. Aos 150 dias de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
12

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
8
0
12
Order By: Relevance
“…Different responses were also observed with the use of mycorrhizal stimulating in other studies (Novais & Siqueira 2009, Cordeiro et al 2015. However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Different responses were also observed with the use of mycorrhizal stimulating in other studies (Novais & Siqueira 2009, Cordeiro et al 2015. However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015).…”
Section: Resultsmentioning
confidence: 70%
“…However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015). This fact becomes important for the Brazilian Savannah region, for mycorrhizal plants have increased resistance to biotic (pests and diseases) and abiotic (water) stress, as several studies have shown (Novais & Siqueira 2009, Ferreira et al 2012, Cordeiro et al 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the area of the first experiment (2010/11), based on the P concentration originally found in the soil (see site characterization above), these three levels of P addition correspond to 0, 75%, and 150% of the P fertilization recommended by Novais et al (1999) for soybean; for the area of the second experiment (2012/13), those three levels of P 2 O 5 addition correspond to 0, 50, and 100% of the recommend P fertilization. The second factor of the factorial scheme consisted of four addition doses of the biostimulant formononetin, 7-hydroxy, 4'-methoxy isoflavone, (0, 25, 50 and 100 g ha -1 ), as the commercial product PHC-506, according to the manufacturers' recommendations (Plant Health Care).…”
Section: Experimental Designmentioning
confidence: 99%
“…The discrepancy in the results from both experiments can be probably attributed to differences in the P levels originally found in the soils from each area. Although the same P levels (0, 60, and 120 kg P 2 O 5 ha -1 ) were used in both experiments, according to the recommendations of Novais et al (1999) they correspond to 0, 75, and 150% of the recommend dose for 2010/11; and 0, 50, and 100% for 2012/13. Therefore, in 2010/11 the intermediate level of P addition was already close (75%) to the recommended dose, while the maximum level of P applied was excessive (150%) for this soil.…”
Section: Productivitymentioning
confidence: 99%